Getting it right, eh? Best practices for post hoc fact-checking in Canadian news - Brooks DeCillia; Brad Clark (Facts & Frictions)
Building on previous research mapping the terrain of the post hoc fact-checking practice in Canadian journalism, this research note evaluates the best methodology for verifying the accuracy of political and other claims and texts. Reviewing fact-checking projects—The Canadian Press Fact Checks, PolitiFact, FactCheck.org, Full Fact, Snopes, and The Washington Post’s Fact Checker—offers several best-checking practices. These include additional research, how fact-checkers should choose the topics they scrutinize (facts, not opinions, often surrounding political campaigns, government, public policy, and health information), and the public interest and balance tests used to select suspicious claims usually made in parliamentary debates, media interviews, campaign speeches, and official records.